GAMBARAN POLA MAKAN SISWA STUNTING DI SMP NEGERI 1 DOLOK MASIHUL TAHUN 2017 - Theresia Sarimauli Siregar; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Malnutrition is caused by inadequate food intake and infectious diseases. Nutritional problems, especially short children, inhibit the development of young people with negative impacts that will take place in the next life. This study aimed to find out the pattern of child eating stunting in SMP Negeri 1 Dolok Masihul. Type of this research was descriptive survey research with cross sectional research design. This study was conducted by calculating the adequacy of energy, protein, calcium, phosphorus, magnesium, zinc vitamin A, vitamin C and iron by using 24 hours food recall method. This sample of research was all students stunting as many as 102 people. The result of this research showed that the stunting student pattern in SMP Negeri 1 according to the amount of food based on the sufficiency of macro nutrient was the sufficiency of energy equal to 98,0% and protein sufficiency equal to 77,5% less category, and for the sufficiency of micro nutrient that was calcium equal to 98, 0%, phosphorus 92,2%, magnesium 65,7%, zinc 97,1%, vitamin A equal to 88,2%, vitamin C equal to 92,2%, iron equal to 99,0% less category. According to the average type of food consumed was 3 types per day and stunting students eat rice as a staple food. Most stunting students often eat fish, eggs and tempeh as side dishes, kale and cassava leaves as vegetables, and bananas as fruit. For the school it was advisable to cooperate with the puskesmas to make an extension activity and make a poster in every class about the importance of consuming diverse food with enough amount every day to catch up the growth of stunting student. Keywords: Dietary Pattern, Stunting, Junior High School Student